Calculation of the Heat Content of the Electrode Metal Droplet When Applying Power Supplies for Manual Arc Welding with Different Volt-Ampere Characteristic - Ilyashchenko D. P. Dmitry Pavlovich (Mechanical Engineering, Processing and Surface Engineereng, Metals Treatment, Equipment and Tools, 2015)
Title screen